La comprensión y la mejora de los centros educativos a través del análisis de sus proyectos de dirección: el caso de Córdoba (España) - García-Segura, Sonia (Universidad de Costa Rica, 2023)
This paper focuses on school management projects within the scope of the administration and management of educational centers. The project management becomes a reality represented by the pedagogical leader on the ideal model of educational center to which he or she aspires, hence the importance of its study. These documents enclose the model of the human being, of the school, and of society in which said leader believes; that is, what is inevitably linked to its educational action. This research, in addition to being of a qualitative nature, focuses on the documentary analysis of nine management projects from different educational centers in the province of Córdoba (four Early Childhood Education and Primary Education and five Secondary Education Institutes) with the aim of explore the discourse of these projects where a characterization of the centers themselves is carried out. The content analysis indicates that these ideas pursue reproduction more than transformation and change within the educational field. The results lead to the conclusion that an authoritarian, normative, and closed discourse continues to exist in these documents, with little evidence of encounter in human values ​​and with limited attention to the principle of attention to diversity. However, it is necessary to highlight the importance given to the participation of the students and the family in the life of the center, as well as the importance of communication and information among the educational community.